Discursive constructions of racism and white privilege in a U.S. pilot seminar. Issue 1 (2nd January 2020) - Putman, Angela L.
ABSTRACT: Utilising discourse from college students who participated in a three-day seminar focused on racism and white privilege that I designed and piloted, this study examines and critiques participants' constructions of these constructs. I collected data via a pre- and post-seminar survey, and through recordings of students' participation in small and large-group discussions, activities, affinity groups, and role-play scenarios. I used a Critical Discourse Analysis approach that most closely follows Fairclough to analyse participants' negotiated constructions of racism and white privilege before, during, and one month after the seminar. I then discussed findings from the study that include participants' subject positionings within the discourse, the implications of students' constructions of racism and white privilege within educational contexts, and how these constructions can reinforce social practices that reify hierarchies, power relations, and status positionings. The paper concludes with implications for scholars and educators who teach courses that examine racism and whiteness.